Ben Jelloun’s Point of View on Racism in the Essay Le Racisme Expliqueé À Ma Fille - Annisa Nitya Pradivta; Diah Kartini Lasman (IAIN MADURA, 2021)
Moroccan literature has been growing since the 1950s, when Morocco was still under French occupation. The big themes that commonly appear in Moroccan literature are the issues of colonialism and racism. One Moroccan writer whose work speaks a lot about racism is Tahar Ben Jelloun. This article aims to analyze one of Ben Jelloun's works entitled Le Racisme expliquée à ma fille. The essay discusses a father and his 10-year-old daughter about racism and what makes people became racist. In the essay, some words are in bold, and these words are mostly phenomena or social events related to the dark history of world civilization due to racism. This study used a qualitative method by using Genette's focalization theory and opposition theory by Greimas markers. The analysis results show that the concept of racism in this essay is conveyed through the father's focalization even though the essay's form is a question and answer between the father and daughter. The selection of forms of dialogue with father and daughter figures can be seen as a narrative strategy to convey the implicit meaning to combat racism. Anti-racism education in the family is Tahar Ben Jelloun's reflection on solutions to racism in the world.